The Influence of Hospital Service Standards on Quality of Life and Level Severity Chemotherapy Induces Nausea Vomiting (CINV) in Breast Cancer Patients - Siti Mu'awanah; Ahsan; Heni Dwi Windarwati (Universitas STRADA Indonesia, 2024)
Background: Globally and in Indonesia, breast cancer is a major cause of both new cases and fatalities. One of the recommended therapies for people with breast cancer is chemotherapy. Measuring the quality of life of breast cancer patients receiving chemotherapy is necessary to evaluate the treatment provided. Side effects of chemotherapy include nausea and vomiting (CINV). Purpose: The purpose of the study is to ascertain how hospital service standards impact the quality of life and severity of chemotherapy-induced nausea and vomiting (CINV) in patients receiving chemotherapy for breast cancer. Methods: A non-equivalent control group design and a quasi-experimental research methodology were employed. The study population included patients with breast cancer receiving chemotherapy at the Baladhika Husada Hospital Jember Chemotherapy Unit and the nearby hospital Soebandi Jember. The study period was 3 weeks and the sample size was 60 patients. Results: The significance value (two-tailed) of WHOQOL from Paired Sample T-Test is less than 0.000 or 0.05, this indicates that his WHOQOL score before and after the exam differed significantly. As for his MAT results, there is no significant difference between the pre-test and post-test phases, as indicated by the significance value p of MAT being more than 1.00 or 0.05. Conclusion: The outcomes demonstrate that while the hospital's standard of has a positive impact on the quality of life but not proven effective in reducing patients' CINV complaints for patients receiving chemotherapy for breast cancer.